2003
DOI: 10.1016/s0010-8804(03)90267-9
|View full text |Cite
|
Sign up to set email alerts
|

The customer's role in the service encounter: The effects of control and fairness

Abstract: Two key elements of service satisfaction for customers are the perception that they have at least some control or choice and that the service provider is being fair. That notion was tested in a video-based experiment in which 50 subjects watched either a restaurant-based or hotel-based scenario that depicted an employee's response to the subject's request for a change in the original order or reservation. In half the scenarios the guest's wish was granted and in half; it was not. Whether the request was grante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 18 publications
3
66
0
Order By: Relevance
“…Based on satisfaction research with client hotels, Schall (2003) discusses best methodological practices for measuring guest satisfaction; the discussed issues include proper sequence and face validity of question items, choice of measurement scales, and appropriate sample sizes for drawing reliable conclusions. Namasivayam and Hinkin (2003) experimented with the degrees of control and fairness perceived by the hotel and restaurant customers in a transaction process and found that the two boundary conditions had both main and interaction effects on customer satisfaction. Barsky and Nash (2003) and Zins (2002) emphasize emotional dominance in satisfaction in an attempt to tie experience-based satisfaction feelings with attitudinal loyalty.…”
Section: Synthesized Reviews Of Topical Significant Trends and Commentsmentioning
confidence: 99%
“…Based on satisfaction research with client hotels, Schall (2003) discusses best methodological practices for measuring guest satisfaction; the discussed issues include proper sequence and face validity of question items, choice of measurement scales, and appropriate sample sizes for drawing reliable conclusions. Namasivayam and Hinkin (2003) experimented with the degrees of control and fairness perceived by the hotel and restaurant customers in a transaction process and found that the two boundary conditions had both main and interaction effects on customer satisfaction. Barsky and Nash (2003) and Zins (2002) emphasize emotional dominance in satisfaction in an attempt to tie experience-based satisfaction feelings with attitudinal loyalty.…”
Section: Synthesized Reviews Of Topical Significant Trends and Commentsmentioning
confidence: 99%
“…Within the service quality domain, the importance of customers" perceptions of service encounters is increasingly recognized (Mill 1986;Namasivayam & Hinkin 2003). In the words of Bitner et al (1994, p. 95), "from the customer"s point of view, the most immediate evidence of service quality occurs in the service encounter or the "moment of truth" when the customer interacts with the firm.…”
Section: Introductionmentioning
confidence: 99%
“…Customer satisfaction with TBSE, by visiting its website, navigating through it, searching for product and service information, is therefore a combination of the customer's satisfaction with the service outcome and with the process of service delivery (Namasivayam and Hinkin, 2003). More specifically, technology developments enable providers to create new services more easily and customers to experience service processes more clearly .…”
Section: Insert Figure 1 Herementioning
confidence: 99%